Visual features of advertising design across cultures: adaptation within the context of globalization - Chebotarova, I. B.; Katrechko, D. O. (ТОВ «Видавництво Ліра-К», 2025)
This paper explores the role of visual code as a carrier of values and meanings in intercultural communication. Particular attention is given to the specific visual presentation of advertising materials in the USA, Japan, and Ukraine as culturally diverse countries. The study examines typographic features, color schemes, composition, and narrative strategies shaped by the sociocultural environment. The importance of adapting visual content to the local context is defined as a prerequisite for effective brand-audience interaction in a globalized market.
Keywords: design; globalization